Enhanced affect/cognition-related brain responses during visceral placebo analgesia in irritable bowel syndrome patients - Lee, Hsing-Feng; Hsieh, Jen-Chuen; Lu, Ching-Liang; Yeh, Tzu-Chen; Tu, Cheng-Hao; Cheng, Chou-Ming; Niddam, David M.; Lin, Han-Chieh; Lee, Fa-Yauh; Chang, Full-Young (Pain (Amsterdam), 2012)
IBS patients and controls achieve comparable placebo analgesia upon experimentally induced rectal pain. The placebo analgesia during the visceral pain involves enhanced brain activities relating to affect/cognition in IBS patients. Placebo analgesia is a psychosocial context effect that is rarely studied in visceral pain. Patients with irritable bowel syndrome (IBS) exhibit visceral hyperalgesia and heightened affective/cognitive brain region activation during visceral stimuli. Psychological factors alter the pain and brain activation pattern, and these changes are more pronounced in IBS patients. Expectation constitutes the major neuropsychological mechanism in the placebo effect. This study confirmed the heightened affective/cognitive brain responses in IBS patients during visceral placebo analgesia using a placebo model with expectation, which was enhanced by suggestion and conditioning. Seventeen IBS patients and 17 age-/sex-matched controls were enrolled. Psychophysical inventories (Hospital Anxiety and Depression Scale [HADS], visual analogue scale, and short-form McGill questionnaire) were completed. Brain activity during placebo intervention and anticipation was assessed in response to rectal distension using 3T-functional magnetic resonance imaging. Suggestion-/conditioning-enhanced placebo was used to convince controls/patients of the efficacy of a newly developed intravenous drug (saline, in actuality) for the relief of rectal distension-induced visceral pain. A comparable visceral placebo analgesia was observed in IBS patients and control subjects. IBS patients demonstrated a higher HADS-anxiety score, which was predictive of a weak placebo effect. Suggestion-/conditioning-enhanced placebo evoked more activity in affective/cognitive brain regions (insula, midcingulate cortex, and ventrolateral prefrontal cortex [VLPFC]) in IBS patients than in healthy controls. VLPFC was also more active during anticipation in IBS patients. In conclusion, IBS patients and control subjects achieved comparable placebo analgesia during experimentally induced rectal pain. The visceral placebo analgesia produced heightened activity in affective/cognitive brain regions in IBS patients.